strategi pengembangan obyek wisata air terjun â€œPutuk Trunoâ€ di kabupaten Pasuruan dengan menggunakan metode analytical hierarki process - Velia Morita Herynda; Hadi Sumarsono (Universitas Negeri Malang, 2022)
Tourism is a type of industry that can increase economic growth by creating jobs and can increase the country's foreign exchange. In developing tourism, related parties are needed in its implementation, such as the participation of the government and the community. As in one of the tourist attractions in Pasuruan Regency, namely the